Pengabdian Masyarakat Tentang Edukasi Pola Konsumsi pada Penderita Diabetes Mellitus di Desa Lueng Ie Kecamatan Krueng Barona Jaya Aceh Besar - Nurul Amna; Khaira Rizki; Ellyza Fazlylawati; Munawarah Munawarah; Fitrah Delvia; Rahil Okfidaria (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Excessive food intake such as carbohydrates/sugar, protein, fat, and energy can be a risk factor for the onset of DM. The purpose of this counseling is to determine the knowledge of the Elderly in Lueng Ie Village, Krueng Barona Jaya District, Aceh Besar. This type of counseling uses the method of providing leaflets, pretests, delivering materials and posttests in the form of filling out questionnaires. The results of the counseling showed that there was a significant increase in knowledge in the Elderly in Lueng Ie Village, Krueng Barona Jaya District, Aceh Besar after being given counseling on Consumption Patterns of Diabetes Mellitus Patients